Ecoepidemiological Model and Analysis of MSV Disease Transmission Dynamics in Maize Plant - Haileyesus Tessema Alemneh; Oluwole Daniel Makinde; David Mwangi Theuri (International Journal of Mathematics and Mathematical Sciences)
In this paper, an ecoepidemiological deterministic model for the transmission dynamics of maize streak virus (MSV) disease in maize plant is proposed and analysed qualitatively using the stability theory of differential equations.The basic reproduction number with respect to the MSV free equilibrium is obtained using next generation matrix approach. The conditions for local and global asymptotic stability of MSV free and endemic equilibria are established. The model exhibits forward bifurcation and the sensitivity indices of various embedded parameters with respect to the MSV eradication or spreading are determined. Numerical simulation is performed and dispalyed graphically to justify the analytical results.